ALOKASI AIR BAKU DAS PAKIJANGAN DI KABUPATEN BREBES - Ikhwanudin; Afifah, Risdiana Cholifatul; Husodo, Ibnu Toto; Wardani, Agustina (Jurnal Teknik Sipil dan Arsitektur, 2026)
The Pakijangan River Basin in Brebes Regency plays a critical role in supplying raw water for domestic, agricultural, and environmental needs. However, the absence of continuous streamflow records and increasing pressure on water resources pose significant challenges to effective management. This study aims to quantitatively estimate water allocation within the basin through a water balance approach. The methodology includes field surveys of existing conditions, analysis of water demand and availability, and water balance simulation using the RIBASIM (River Basin Simulation) model integrated with the Sacramento rainfall-runoff method. Rainfall data were obtained from two representative manual stations: Klampok and Slatri. Simulation results indicate that the Pakijangan Basin remains in surplus throughout the year, with dependable flow sufficient to meet all domestic and non-domestic water demands. With a distribution efficiency indicator (K factor) of 1, the basin even has the capacity to supply neighboring basins (Pemali River Basin) at a rate of 0.1 mÂ³/s. These findings serve as a valuable foundation for sustainable, equitable, and efficient water resource planning and management in the region